Natural Anthraquinones as Potential Akt1-Targeted Anticancer Agents - Shokoofeh Jamshidi; Fatemeh Mahfouzi; Setareh Shojaei; Amir Taherkhani (Avicenna Journal of Medical Biochemistry)
Background: The phosphoinositide 3-kinase/protein kinase B (Akt)/mammalian target of the rapamycin signaling pathway is crucial in cancer progression. Akt1, a vital pathway component, has emerged as a promising therapeutic target.